2015
DOI: 10.1007/s00412-015-0549-2
|View full text |Cite
|
Sign up to set email alerts
|

FancJ (Brip1) loss-of-function allele results in spermatogonial cell depletion during embryogenesis and altered processing of crossover sites during meiotic prophase I in mice

Abstract: Fancj, the gene associated with Fanconi anemia (FA) Complementation Group J, encodes a DNA helicase involved in homologous recombination repair and the cellular response to replication stress. FANCJ functions in part through its interaction with key DNA repair proteins, including MutL homolog-1 (MLH1), Breast Cancer Associated gene-1 (BRCA1), and Bloom syndrome helicase (BLM). All three of these proteins are involved in a variety of events that ensure genome stability, including the events of DNA double strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 71 publications
7
33
4
Order By: Relevance
“…Prophase I spermatocyte chromosome spreads were performed as previously described (Sun et al, 2015). Primary antibodies included: rabbit anti-Sororin (anti-Sororin serum C-106 was generated using a full-length recombinant mouse protein cloned in pET-12a vector and expressed in E. coli (Carretero et al, 2013)), anti-mouse SYCP3 (ab97672), rabbit anti-PDS5B (ab84918) (both from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Prophase I spermatocyte chromosome spreads were performed as previously described (Sun et al, 2015). Primary antibodies included: rabbit anti-Sororin (anti-Sororin serum C-106 was generated using a full-length recombinant mouse protein cloned in pET-12a vector and expressed in E. coli (Carretero et al, 2013)), anti-mouse SYCP3 (ab97672), rabbit anti-PDS5B (ab84918) (both from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Our data presented here demonstrate age-related upregulation of pathways associated with DNA replication and repair, double strand break repair, and response to DNA damage, all of which may underlie the well-characterized differences between spermatocytes in the first wave compared to steady-state spermatocytes. Included in these sets of variably-expressed genes are known regulators of DNA damage response and cross-over formation including Rad51 33 , Brip1 29 , and H2afx 34 , as well as Brca1 and Brca2 3032 and Atm 35,59 , all of which increase in spermatocytes with age, effects which we have also shown at the protein level for both RAD51 and ATM ( Figures 10, S11, S12 ). While the cause of this lower expression in the first wave is unknown, it has been demonstrated that spermatocytes from juvenile mice generate only about 25% of the double strand breaks present in spermatocytes from steady-state spermatogenesis 59 .…”
Section: Discussionmentioning
confidence: 59%
“…From this analysis, we observe decreasing expression of genes related to translation and post-transcriptional regulation, and increasing expression of genes related to DNA replication, double strand break repair, and cell cycle regulation ( Figure 7 & S6B, Table S6 ). Most notable in the list of genes upregulated in spermatocytes of increasing age are those known to be essential to DNA repair, meiotic progression, and crossover formation including Brip1 29 , Brca1 and Brca2 3032 , Rad51 33 , H2afx 34 and Atm 35 . Many of these pathways, particularly those related to double strand break repair (which initiates meiotic recombination), may be crucial for understanding the molecular mechanisms underlying fundamental differences in first-wave spermatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…During the germ cell reproductive process, epigenetic chromatin modifications such as methylation, acetylation and ubiquitination play major roles (Gannon et al, 2014). (Guo et al, 2018;Simhadri et al, 2014;Sun et al, 2016;Ward et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In dividing cells HR predominantly occurs in mitotic S phase cells to maintain DNA fidelity During meiosis phase 1 the many double strand breaks generated during crossover are also repaired by HR (Cohen and Pollard, 2001;Roeder, 1997). Loss of HR repair related proteins, therefore, (such as 53BP1, RIF1, BRCA1, ATM, MOF) affects spermatogenesis (Bartkova et al, 2001;Jiang et al, 2018;Marcet-Ortega et al, 2017;Pandita et al, 1999;Schwab et al, 2013;Sun et al, 2016). Cbx1 -/mice display prenatal death due to severe alveoli lung damage and abnormal neuromuscular and cerebral cortex tissue development (Aucott et al, 2008).…”
Section: Introductionmentioning
confidence: 99%